2013
DOI: 10.1007/s00795-013-0013-4
|View full text |Cite
|
Sign up to set email alerts
|

Implications on glycobiological aspects of tumor hypoxia in breast ductal carcinoma in situ

Abstract: Breast carcinoma is one of the most common neoplasia and the first cause of women cancer related deaths worldwide. In the past few years with diagnostic increment, the number of patients diagnosed with ductal carcinoma in situ (DCIS) increased considerably and opened up new ways in research and new dilemmas in diagnostic and clinical practice. This work aimed to evaluate differences in Galectin-1 and Galectin-3 expression and lectins ligands profile on DCIS cells in hypoxic microenvironment. Lectin histochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…We also observed that Gal-1 expression was found mainly in the extracellular matrix and tumor-associated stromal cells, demonstrating their importance in the relationship between a tumor and its microenvironment [226, 227]. …”
Section: Hypoxia Alters Cell Location Of Galectins and Interaction Wimentioning
confidence: 99%
“…We also observed that Gal-1 expression was found mainly in the extracellular matrix and tumor-associated stromal cells, demonstrating their importance in the relationship between a tumor and its microenvironment [226, 227]. …”
Section: Hypoxia Alters Cell Location Of Galectins and Interaction Wimentioning
confidence: 99%
“…This carefully orchestrated modulation of glycan diversity during development implies corresponding and important functions for these molecules (1,12). There is evidence that glycan structures reflect their evolutionary backgrounds and functional aspects in various contexts, including differentiation, development, fertilization, inflammation, cell adhesion, and cell-cell recognition (13).…”
Section: Introductionmentioning
confidence: 99%
“…In some specific environments, such as necrotic areas, Gal-3 and its ligands are overexpressed in glioblastoma in hypoxic regions known as pseudopalisades [39], as well as in regions around necrotic areas from ductal carcinoma in situ of the breast, as demonstrated in a previous study by our group [12]. Another interesting result was the low immunopositivity of staining with M338 antibody which recognizes N-terminal region of Gal-3, a fact which could be relate to N-terminal cleavage performed by matrix metalloproteinases, as well as phosphorylation in hypoxic regions [40,41].…”
Section: Discussionmentioning
confidence: 90%
“…The excess reagent was removed in two baths of phosphate-buffered saline (PBS) for 5 min, the peroxidase color reaction was developed with diaminobenzidine-H 2 O 2 (DAB) and the nuclei were counter-stained with hematoxylin. Samples of ductal carcinoma in situ of the breast previously known to be positive for lectin histochemistry were used as positive controls, while the negative control was obtained by replacing the lectin with PBS and lectin inhibition with its specific sugar at a concentration of 300 mM [12,13]. All materials which source was not specified were obtained from SigmaAldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation